Sistem Informasi Administrasi Kemahasiswaan dan Alumni (Smart Adma) dengan Metode Extreme Programming (XP) - Wahyuddin, Mohammad Iwan; Aldisa, Rima Tamara; Fauziah, Fauziah; Sholihati, Ira Diana (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
The purpose of this research is to develop a website-based system to facilitate the academic administration of student affairs at the Faculty of Information Communication Technology, Universitas Nasional in providing various student information ranging from information on association activities, scholarships, competitions, achievements achieved by FTKI (SI-TI) students. and helping FTKI students and graduates to find updated information about job vacancies related to information technology. This study will develop an administrative information system for student affairs with the Extreme Programming method, an Agile Development Method. will include FTKI students and graduates as users. The results of research from the Student and Alumni Administration Information System (Smart Adma) can provide time efficiency in administrative management, make it easier for students to get information from association activities, proposals, requests for funds to submission forms and internship assessments, as well as alternative media during the Covid 19 Pandemic.Keywords:Information Systems, Smart AdMa, Extreme Programming Method (XP).